2019
DOI: 10.1177/0891988719865345
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health-Care Delivery for Older People in China: An Update of Challenges and Recent Clinical Research

Abstract: China is facing rapid population aging and the country has the world's largest aging population. The rapid demographic shift in aging population is associated with many social and health problems, in particular mental health issues. The aim of this article is to summarize the challenges and recent progress in mental health-care delivery and clinical research for older people in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Limitation of resources in MH is the result of poor economic condition, low priority of MH, and deficient stewardship (10). Insufficiency of resources for providing MH services can be categorized as inadequate financial resources (12,39), lack of enough professionals (40) particularly at the primary level (60), shortage of medications (42), and limited service delivery facilities (43).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Limitation of resources in MH is the result of poor economic condition, low priority of MH, and deficient stewardship (10). Insufficiency of resources for providing MH services can be categorized as inadequate financial resources (12,39), lack of enough professionals (40) particularly at the primary level (60), shortage of medications (42), and limited service delivery facilities (43).…”
Section: Discussionmentioning
confidence: 99%
“…A-1-1-Insufficient resources: results of the analysis showed that lack of sufficient resources was the most frequent barrier regarding the provision of MH services. Findings indicated that scarcity of resources for MH services in LMICs can be classified into four main categories including restricted financial resources (12,15,33,35,39), shortage of adequate MH professionals (33)(34)(35)(38)(39)(40), insufficiency of medications (42), and limited healthcare facilities (13,33,42,43).…”
Section: A-1-resource and Administrative Barriersmentioning
confidence: 99%
See 3 more Smart Citations